SEN Policies and migrant children in Italian schools: micro-exclusions through discourses of equality. Issue 6 (1st November 2020) - Migliarini, Valentina; D'Alessio, Simona; Bocci, Fabio
ABSTRACT: This article analyses the underpinnings and implementation of Special Educational Needs (SEN) policies in Italy, within the internationally celebrated policy arena of Integrazione Scolastica (i.e. school integration), through an equity prism. The aim is to explore the extent to which SEN policies in Italy foster inclusion and equity in education, particularly when targeting migrant children. In doing so, the paper intends to advance critical thinking about the recent phenomenon of over-representation, or 'SENitization', of students from migrant backgrounds within the SEN macro-category in Italy, by examining policy narratives both nationally and locally. Analysing the policies through the intersectional lens of Disability Critical Race Theory in education framework, this article suggest that Italian SEN policies legitimates forms of micro-exclusions of migrant students in mainstream classrooms, despite discursive promises of equality for all students.